Class rank [videorecording (DVD)] - Gisondo, Skyler; Holt, Olivia, 1997-; Chenoweth, Kristin; Dern, Bruce (VMI, 2018)
Two high school outsiders, Veronica, a type-A personality with Ivy League aspirations and Bernard, a quirky nerd, join forces in an attempt to overtake the local school board and eliminate the class-ranking system. Guided by their families, the two enter the perilous word of politics and, in the process, learn a thing or two about love.